For the century's end : poems, 1990-1999 - Haines, John, 1924-2011 (The Pacific Northwest poetry series., 2001)
New poems by the much-honored author of 14 books of poetry & 5 books of essays, now a resident of Missoula, Montana, after living many years in the Alaskan wilderness. This is the first volume in the invitational Pacific Northwest Poetry Series, edited by Linda Bierds.